RELASI IDEOLOGI, KEKUASAAAN, DAN MEDIA - Candra, Supriyanto (Universitas Nurul Jadid, 2014)
The media is actor of important politic that capable shape how the public think and feel about various of event and experience. This is where the ideology and power entry into it. The ideology and power can’t released from power of business and economic. Travel minority the muslim of Melayu in this Southern Thailand is travel of long search for identity. The complexity the history of violence in this Southern Thailand that reported by “The Nation” reflect a relation of ideology, power and media. The issues of justice society of economic very strong be expressed in every event of upheaval. However from analysis that depth, we encountered factors that more complex from just issue of social ekonomic. However we found also in there a factors for example psychology, social, local police, and culture islamic, a aspiration that play role in every event violence in this regional.